Pengaruh Konsumsi Energi dan Aktivitas Ekonomi Terhadap Emisi CO2 di Negara G20: (The Effect of Energy Consumption and Economic Activity on CO2 Emissions in G20 Countries) - Naufaliztya Aulia Tsandra; Ridwan Pandu Sunaryo; Syafri Syafri; Dian Octaviani (e-Journal Ekonomi Bisnis dan Akuntansi, 2023)
As a multilateral cooperation forum, the G20 plays a central role in contributing to the reduction of the global climate change rate, with a primary goal of lowering CO2 emissions. This study examines the effect of energy consumption and economic activity on CO2 emissions in Advanced Economies and Emerging Markets countries that are members of the G20, and to identify countries that have an impact on CO2 emissions. The data used in this study is secondary data from Our World In Data database with yearly data for 2000-2021. The analysis method used in this research is a quantitative approach with panel data regression analysis method with the Fixed Effect Model (FEM). The findings indicate that in Advanced Economies countries, CO2 emissions are affected by fossil fuel energy consumption, renewable energy consumption, GDP per capita, and trade openness. Meanwhile, CO2 emissions in Emerging Markets countries are affected by fossil fuel energy consumption, renewable energy consumption, GDP per capita, FDI, and industrialization. The country with the highest CO2 emissions per capita is Australia, while the country with the lowest CO2 emissions per capita is India.